The ASR mechanism of reactive aggregates in concrete and its mitigation by fly ash: A critical review - Saha, A.; Khan, M.; Sarker, Prabir; Shaikh, Faiz; Pramanik, Alokesh (Elsevier BV, 2018)
Alkali-silica reaction (ASR) of reactive aggregates is a major durability concern of concrete. The use of fly ash as a supplementary cementing material (SCM) shows a reliable way to control ASR expansion. This paper investigates the recent findings on effects of coal fly ash as a SCM on ASR of reactive aggregates. ASR is the reaction of amorphous silica of aggregates with highly alkaline pore solution in the binder matrix producing an expansive gel. The use of fly ash as cement replacement reduces pH of the pore solution by alkali binding and thus reduces the aggregate dissolution rate and swelling pressure of the ASR gel. The efficiency of fly ash primarily depends on its chemical composition with low calcium fly ash being more effective in mitigation of ASR expansion. Based on the available literature, this paper also analyses the ASR mitigation mechanisms of fly ash and provides some recommendations for future research. The degree of aggregate reactivity measurement, effect of alumina in fly ash, swelling properties of ASR gel in presence of fly ash and the long-term alkali contribution of fly ash on ASR are of particular importance.